FIRST EVIDENCE FOR LATE NORIAN PROGRADATION OF JULIAN PLATFORM TOWARDS SLOVENIAN BASIN, EASTERN SOUTHERN ALPS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2014)
The Late Triassic in the Southern Alps is marked by an extensive growth of carbonate platforms. Whereas Dolomia Principale dominates the western and central sections, Dachstein Limestone dominates the eastern side of the Southern Alps on the so-called Julian Platform in what is now NW Slovenia. Younger tectonic movements greatly deformed the original configuration of the Julian Platform and its margins are consequently poorly preserved. While late Tuvalian and early Norian platform progradation has been recorded on the northern and eastern side of the platform, no such information is available for the southern edge of the platform, where it borders the deeper Slovenian Basin. Three detailed sedimentological sections from the southern slopes of the Jelovica plateau span from the top of the basinal Bača dolomite to the Slatnik Formation and the prograding slope of the Dachstein Limestone. The progradation has been dated as late Norian in age, and can be correlated to a poorly-expressed coarsening event recorded in previously known sections of the Slovenian Basin. In contrast to deeper parts of the basin, shallow water conditions were established on the Jelovica plateau by the beginning of the Rhaetian.